Associations of Functional MicroRNA Binding Site Polymorphisms in IL23/Th17 Inflammatory Pathway Genes with Gastric Cancer Risk. (8th October 2017) - Dong, Kaiyan; Xu, Yajuan; Yang, Qian; Shi, Jiachen; Jiang, Jicheng; Chen, Yi; Song, Chunhua; Wang, Kaijuan
Abstract : IL23/Th17 axis acts as an inflammatory pathway in gastric carcinogenesis. MicroRNA- (miRNA-) binding site single-nucleotide polymorphisms (SNPs) of inflammatory genes may alter gastric cancer (GC) susceptibility. In this study, four miRNA binding site SNPs (rs3748067 of IL17A, rs887796, rs1468488 of IL17RA, and rs10889677 of IL23R ) were genotyped from 500 patients and 500 controls. Unconditional logistic regression analyses and multifactor dimensionality reduction software were used to evaluate the relationships of SNPs with GC and gene-environment interactions, respectively. Quantitative real-time PCR, Western blot analysis, and luciferase report gene assay were applied for function verification. We found that CT (ORadj  = 0.59; 95% CI: 0.44–0.79), CT + TT (ORadj  = 0.58; 95% CI: 0.43–0.77) genotypes, and T allele (ORadj  = 0.77; 95% CI: 0.47–0.80) of rs3748067 reduced GC risk; the rs10889677 CC genotype (ORadj  = 2.22; 95% CI: 1.27–3.87) and C allele (ORadj  = 1.24; 95% CI: 1.02–1.52) increased GC risk. A meaningful interaction among ever smoked, family history of GC, and rs3748068 could intensify GC risk by 2.25-fold. Functional tests demonstrated the inhibitory effect of miR-10a-3p on IL17A expression in SGC-7901 cells. These results suggested that miRNA binding site SNPs within IL23/Th17 inflammatory pathway genes and their interactions with environmental factors could be associated with GC risk.